Brine shrimp lethality test of various Cinnamomum iners (Lauraceae) barks extracts (Journal of Tropical Resources and Sustainable Science (JTRSS), 2018)
Cinnamomum iners (Lauraceae) is a traditional plant that widely used to relieve headache, breathing and appetite problems. This plant has been used over the centuries on several illnesses with bacterial symptoms such as fevers, digestive ailments and coughs. However, lack of scientific studies have been conducted to identify its toxicity. Thus, an evaluation on the toxicity of this plant extracts is crucial to support its therapeutic claims as well as to ensure that there was no side effects to consumers. Various extracts from C. iners barks were screened for their toxicity against brine shrimp using the brine shrimp lethality test. All extracts exhibited very high LC50 (50% lethal concentration) values greater than 1mg/ml (1000 g/ml) with the hexane extracts showed the highest toxicity to the brine shrimp with LC50 value of 1306.79 g/ml, while the lowest toxicity was the ethyl acetate extract at 3370.13 ?g/ml. This finding corroborates the traditional uses of this plant and could be developed as another alternative natural sources in treating various diseases.
Keywords: Brine shrimp lethality test; Cinnamomum iners